Palinotaxonomy of Passiflora section Xerogona (Passifloraceae) - Milward-De-Azevedo, Michaele Alvim; de Souza, Fabiana Carvalho; Gonçalves-Esteves, Vania; Kinoshita, Luiza Sumiko (Phytotaxa, 2014)
Passiflora sect. Xerogona is a tropical and subtropical group comprising 14 species that occur in tropical and Atlantic forest domains throughout Latin America. The section is characterized by herbaceous vines bearing leaves without petiole glands or bracts, leaf blades without ocelli, and capsular fruits. The pollen grains of 13 species of this section were acetolysed and subsequently measured, described, and photographed. The taxa have large or medium sized pollen grains that are isopolar, prolate spheroidal, prolate, oblate spheroidal, spherical or subprolate, 12-colpate, 12-colporate or 6-colporate, 3 or 6 mesocolpium, with the presence or absence of an operculum, pseudoperculum, and secondary operculum, and with exineheteroreticulate. A key to the species based on pollinic data is presented, demonstrating that pollinic characteristics are important in the taxonomy of Passiflora.